The Life of the Terrorist Convicts’ Wives: Unequal Family Dynamics and Islamic Legal Frameworks - Zakiyah, Zakiyah; Muzayanah, Umi; Noviani, Nur Laili (AHKAM : Jurnal Ilmu Syariah, 2025)
This article discussed the lives of the wives of terrorist convicts, including their everyday lives, and the relationship between the wives and their husbands in the terrorist offenders’ families. This theme is important to be examined for the following reasons: Indonesia has experienced a series of bombing actions throughout the country, and the existing studies mainly describe the actors who are mostly men affiliated with radical groups. This article was written based on field research in six places in Indonesia, including Lamongan, Surabaya, Madiun, Bojonegoro (East Java), Surakarta (Central Java), and Yogyakarta. Data were collected using interviews, observations, and documentary studies. The results of this study revealed that the wives of terrorist offenders faced difficulties in their lives, such as economic difficulties as they became the main breadwinners for the family, and they faced stereotyping as the families of terrorist offenders. Furthermore, there were unequal relationships between the wives and the husbands; for instance, most of the wives did not know their husbands' activities related to terrorist actions. This belief is supported by interpretations of Islamic law, which assert that men are leaders with full authority to manage their families and oversee their wives and children.   Abstrak: Artikel ini membahas tentang kehidupan istri narapidana teroris, termasuk kehidupan sehari-harinya, serta bagaimana hubungan istri dan suami dalam keluarga pelaku teroris. Tema ini penting untuk dikaji karena beberapa alasan berikut; Indonesia pernah mengalami serangkaian aksi pengeboman yang tersebar di beberapa wilayah di tanah air, dan kajian yang pernah dilakukan, terutama menggambarkan pelaku terorisme yang sebagian besar adalah laki-laki yang berafiliasi dengan kelompok radikal.  Artikel ini ditulis berdasarkan penelitian lapangan di enam wilayah di Indonesia meliputi, Lamongan, Surabaya, Madiun, Bojonegoro (Jawa Timur), Surakarta (Jawa Tengah), dan Yogyakarta. Data dikumpulkan dengan menggunakan metode berikut ini; wawancara, observasi, dan studi dokumenter. Hasil penelitian ini menunjukkan bahwa istri pelaku terorisme menghadapi kesulitan dalam hidupnya, seperti kesulitan ekonomi karena mereka menjadi pencari nafkah utama keluarga dan mendapat stereotip sebagai keluarga teroris. Selain itu, terdapat hubungan yang timpang antara istri dan suami, misalnya sebagian besar istri tidak mengetahui aktivitas suaminya terkait aksi teroris. Kondisi ini diperkuat dengan adanya justifikasi yang dirujuk dari ajaran Islam, yakni interpretasi terhadap hukum Islam yang menjelaskan laki-laki adalah pemimpin dan mempunyai otoritas penuh untuk mengelola keluarga dan mengontrol istri dan anak-anaknya.